خيارات تنفيذ مشاريع تنمية الأقاليم: دراسة تحليلية مقارنة في محافظة كربلاء المقدسة - القيسي، نسرين سبع خميس; فارس، علي أحمد (جامعة تكريت - كلية الإدارة والاقتصاد, 2023)
هدفت هذه الدراسة إلى قياس وتحليل مدد إنجاز الأهداف المخطط لها والفعلية، فضلا عن تحليل مدى تباين الأهداف المنجزة من ناحية التخصيصات، وتحديد الخصائص الرئيسية للمشاريع والبرامج الحكومية، والتوصية بكيفية استخدامها لتحسين الأداء، ولعدم وجود أهداف واضحة ومحددة تم تبنيها من قبل إدارة المحافظة عند تنفيذ عملية التطوير. فضلا عن عدم الاعتماد على مؤشرات الأداء التي تحقق العدالة المالية والزمنية في توزيع مخصصات برنامج التنمية الإقليمي. ولغرض تحليل الخيارات المتاحة لتنفيذ مشاريع تنمية الأقاليم تم تحليل (5) قطاعات خدمية من أصل 12 قطاع في محافظة (كربلاء المقدسة) بالاعتماد على البيانات والتقارير الرسمية الصادرة من الدوائر المختصة والمعنية بتنفيذ مشاريع التنمية، فضلا عن قواعد البيانات والمؤشرات التنموية الصادرة من قسم الجهاز المركزي الإحصائي وقسم التنمية البشرية في وزارة التخطيط العراقية للمدمة من 2008 إلى 2022م. وبعد مقارنة جميع الخيارات المتاحة في كل مشروع من مشاريع هذه القطاعات، تبين أنه لم يتم مراعاة التخصيصات والزمن في تنفيذ المشاريع الخاصة بكل منها، حيث إن بعض التخصيصات المقدرة للمشاريع بعيدة عن التكاليف الفعلية، فضلا عن عدم وجود تحكم بوقت بدء تنفيذ المشروع وإنهاؤه، أي إنه لا توجد جدولة مدروسة للمشاريع التنموية، ولغرض الحصول على نتائج حقيقية ودقيقة تغني الجانب العملي للدراسة الحالية فقد تم التحليل الكمي للبيانات وفق معياري (المدد والتخصيصات المالية) بالاستناد على الأوساط الحسابية والأشكال البيانية وكذلك استخدام معامل جيني (Gini Coefficient) في تحليل البيانات الخاصة بالقطاعات الداخلة ضمن إطار البحث والتي أظهرت تلكؤ وتعثر واضح في تنفيذ المشاريع والافتقار إلى التخطيط والتقدير الزمني والمالي في أغلب مشاريع القطاعات التي اتخذت كعينة لهذا البحث، فضلا عن عدم وجود عدالة في توزيع الاستثمار بين القطاعات الخدمية. This study aimed at measuring and analyzing the duration of achievement of the planned and actual goals, as well as analyzing the extent of the variation in the achieved goals in terms of allocations, identifying the main characteristics of government projects and programs, and recommending how to use them to improve performance, and due to the lack of clear and specific goals that were adopted by the governorate administration when implementing development process. As well as not relying on performance indicators that achieve financial and temporal justice in the distribution of allocations for the regional development program. For the purpose of analyzing the options available for the implementation of regional development projects, (5) service sectors out of 12 sectors were analyzed in the Holy Karbala Governorate, based on official data and reports issued by the competent departments concerned with the implementation of development projects, in addition to the databases and development indicators issued by the Central Apparatus Department. Statistician and Human Development Department in the Iraqi Ministry of Planning for the period from 2008 to 2022 AD. After comparing all the options available in each of these sectors’ projects, it was found that the allocations and time were not taken into account in the implementation of the projects for each of them, as some of the estimated allocations for projects are far from the actual costs, in addition to the lack of control over the start and end time of project implementation, ie There is no well-studied scheduling of development projects, and for the purpose of obtaining real and accurate results that enrich the practical side of the current study, the quantitative analysis of the data was carried out according to the criteria (periods and financial allocations) based on the arithmetic mean and graphic figures, as well as the use of the Gini coefficient in analyzing the data of the sectors Included within the framework of the research, which showed clear delay and stumbling in the implementation of projects and the lack of planning and time and financial assessment in most of the projects of the sectors that were taken as a sample for this research, as well as the lack of justice in the distribution of investment between the service sectors.
Keywords: القطاعات الخدمية -- المشاريع التنموية -- تنمية الأقاليم -- العراق